2014
DOI: 10.1007/s11051-014-2677-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel nanopesticide and its potential toxic effect on soil microbial activity

Abstract: A new nanopesticide, carboxymethyl-bcyclodextrin-Fe 3 O 4 magnetic nanoparticles-Diuron (CM-b-CD-MNPs-Diuron), was synthesized from an inclusion complex of CM-b-CD-MNPs as host and diuron as guest molecules. The transmission electron microscopy revealed it had an average diameter of 25 nm which is more or less the same as that of MNPs (average diameter *23 nm). The CM-b-CD grafting was confirmed by infrared spectroscopy, and the amount of CM-b-CD grafted on the surface of MNPs was determined to be 144.1 mg/g b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…42 For instance, similar increased toxicity to microbial enzyme activity was observed when applying carboxymethyl-β-cyclodextrin-Fe 3 O 4 magnetic nanoparticles-diuron as a nano-pesticide in soil. 43 We further demonstrated that the NPATZs might also potentiate the activity of ATZ against the non-target rhizosphere bacterial community. The enhanced biological activity of NPATZs could be attributed to the delivery efficiency of ATZ to the rhizosphere microbial communities e.g.…”
Section: Discussionmentioning
confidence: 68%
“…42 For instance, similar increased toxicity to microbial enzyme activity was observed when applying carboxymethyl-β-cyclodextrin-Fe 3 O 4 magnetic nanoparticles-diuron as a nano-pesticide in soil. 43 We further demonstrated that the NPATZs might also potentiate the activity of ATZ against the non-target rhizosphere bacterial community. The enhanced biological activity of NPATZs could be attributed to the delivery efficiency of ATZ to the rhizosphere microbial communities e.g.…”
Section: Discussionmentioning
confidence: 68%
“…However, low urease activity was observed in soils spiked with diuron [52], but, on the contrary, Liu et al [53] observed inhibition of this enzymatic activity. Such difference may be explained by the different diuron rates used in these studies: 3 mg kg -1 in Fernandez-Bayo's study [52] and 5000 mg kg -1 in Liu`s [53].…”
Section: Diuronmentioning
confidence: 88%
“…While the impact of metal and metal oxide nanoparticles on the soil microbiota as non-target organism have been addressed in the literature, those of nanoformulation of pesticides still stay poorly documented. Liu et al (2014) synthesized a new nanopesticide CM-ß-CD-MNPs-Diuron (average diameter of 25 nm by TEM) from an inclusion complex of cyclodextrin-Fe3O4 magnetic nanoparticles as host and diuron as guest molecules. Their potential toxic effects on soil microbiota was evaluated by microcalorimetry, measure of urease enzyme activity and qPCR.…”
Section: Impact Of Nanopesticides On Non-target Soil Microorganims and Microbiomesmentioning
confidence: 99%